2022
DOI: 10.1002/dys.1714
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions in Chinese kindergarten children with early reading problems

Abstract: Learning to read Chinese is a complex task that draws on a range of executive function (EF) skills since early development. However, no studies have examined EF as a potential contributing factor to early reading problems among Chinese children. The present longitudinal study identified 48 poor readers and 48 normal readers among a sample of 190 Chinese children at the end of kindergarten. Measures of EF skills (working memory, inhibition control, and cognitive flexibility) and reading outcomes (word reading, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…The development of cognitive flexibility begins at the age of 2 and gradually progresses between ages 3 and 5 [40][41][42]. Research has found that the cognitive flexibility of 4-to 5-year-old children can influence their reading comprehension and predict the reading performance of these developing readers [43,44]. Studies have indicated that cognitive flexibility may promote the development of individual phonological awareness, and consequently enhance reading ability [38,45].…”
Section: The Relationship Between Cognitive Flexibility Inhibitory Co...mentioning
confidence: 99%
“…The development of cognitive flexibility begins at the age of 2 and gradually progresses between ages 3 and 5 [40][41][42]. Research has found that the cognitive flexibility of 4-to 5-year-old children can influence their reading comprehension and predict the reading performance of these developing readers [43,44]. Studies have indicated that cognitive flexibility may promote the development of individual phonological awareness, and consequently enhance reading ability [38,45].…”
Section: The Relationship Between Cognitive Flexibility Inhibitory Co...mentioning
confidence: 99%